Ruling the Land of the Yellow Lama: Religion, Muli, and geopolitics in the 17th century Sino-Tibetan borderland. Issue 2 (3rd April 2019) - Hu, Xiaobai
Abstract: The author scrutinizes the history of Muli (木里) as a semiautonomous political entity in the 17th century southern Sino-Tibetan borderland. By tracing Muli's improvization in the face of multiple powerful regimes such as the Naxi kingdom, the Geluk Tibetans, the Khoshut Mongols, and the Chinese dynasties, the author explores how an indigenous notion of power took shape in the wake of geopolitical turbulence. Before 1580, Muli was a colony of the Naxi kingdom and dominated by the Kagyu school of Tibetan Buddhism. After 1640, it became a stronghold of the Tibetan Buddhist Geluk school and was deeply involved in the power struggles between the Geluk and Kakyu schools as well as the Tibetans and Mongols. Despite of acknowledging multiple sovereigns, Muli rulers utilized various tactics to hold on to power and prioritize local interest. The nuanced, yet creative, strategies Muli people adopted showcases the significant role border regimes played and their agency in shaping the power dynamics in pre-modern Eastern Asian borderlands.